Streptomyces sp. 17, an Organism Producing Oligomycin SC-II (Culture Characteristics and Antibiotic Biological Properties) - Ì. V. Bibikovà; N. E. Grammatikova; I. À. Spiridonova; À. N. Dànilenko; À. V. Katlinsky (Антибиотики и Химиотерапия, 2020)
Under the screening programme for organisms producing substances with hypolipidemic and antifungal activity Streptomyces sp. 17 was isolated. The taxonomic properties of the strain were investigated. Active compounds, i.e. oligomycin A and oligomycin SC- II were isolated from a complex biosynthetic product. Oligomycin A showed high antifungal activity whereas oligomycin SC-II had also moderate antibacterial activity.